2016
DOI: 10.1055/s-0042-108201
|View full text |Cite
|
Sign up to set email alerts
|

Injury Patterns among Elite Football Players: A Media-based Analysis over 6 Seasons with Emphasis on Playing Position

Abstract: The study objective was to describe the types, localizations and severity of injuries among first division Bundesliga football players, and to study the effect of playing position on match and training injury incidence and severity, based on information from the public media. Exposure and injuries data from 1 448 players over 6 consecutive seasons were collected from a media-based register. In total, 3 358 injuries were documented. The incidence rate for match and training injuries was 11.5 per 1 000 match-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 40 publications
2
72
1
9
Order By: Relevance
“…All data were collected between July and October 2017. A recently published validation study elegantly demonstrated sufficient validity and accuracy of the injury related data retrieved from Transfermarkt.de . An inter‐observer agreement of over 90% between reference sources and Transfermarkt.de and a Cohen's kappa of 0.82 for cross‐validation were found …”
Section: Methodsmentioning
confidence: 80%
“…All data were collected between July and October 2017. A recently published validation study elegantly demonstrated sufficient validity and accuracy of the injury related data retrieved from Transfermarkt.de . An inter‐observer agreement of over 90% between reference sources and Transfermarkt.de and a Cohen's kappa of 0.82 for cross‐validation were found …”
Section: Methodsmentioning
confidence: 80%
“…The football magazine ‘kicker Sportmagazin’ is published twice weekly with one journalist being responsible for one club and usually having contact with the club every day. Similarly, online open-source sports databases and the diagnoses being communicated to these media by team officials have previously been used to gather information on injuries in professional football 17 32. Yet the present data were not validated with medical records by each team’s medical departments.…”
Section: Discussionmentioning
confidence: 91%
“…The time to return to unrestricted practice was defined based on the number of days absent from sport as adopted from transfermarkt and reported by Schiffner et al 19. The time to return to competition was defined as the time from injury to the participation of at least 1 min of an official match, as reported in online sources.…”
Section: Methodsmentioning
confidence: 99%
“…Walden and colleagues,18 in their milestone 15-year UEFA study on return to sport after ACL injury, included data from the website transfermarkt and the club's official website. The reliability of the data from transfermarkt has been validated by other online reference sources without the use of official medical reports 19…”
Section: Introductionmentioning
confidence: 99%